Helminth Mediated Attenuation of Systemic Inflammation and Microbial Translocation in Helminth-Diabetes Comorbidity - Rajamanickam, Anuradha; Munisankar, Saravanan; Menon, Pradeep A.; Dolla, Chandrakumar; Nutman, Thomas B.; Babu, Subash (Frontiers in Cellular and Infection Microbiology, 2020)
Type 2 diabetes mellitus (T2DM) is characterized by heightened systemic inflammation and microbial translocation. Whether concomitant helminth infections can modulate this systemic response is unclear. We examined the presence of markers of systemic inflammation (levels of acute phase proteins) and of microbial translocation [levels of lipopolysaccharide (LPS) and its associated products] in T2DM individuals with (Ss+) or without (Ss−) Strongyloides stercoralis (Ss) infection. We also analyzed these parameters at 6 months following anthelmintic treatment in Ss+ individuals. Ss+ individuals exhibited significantly diminished levels of alpha-2 macroglobulin, C-reactive protein, haptoglobin and serum amyloid protein A1 compared to Ss− individuals and these levels increased significantly following therapy. Similarly, Ss+ individuals exhibited significantly diminished levels of LPS, sCD14, intestinal fatty acid binding protein, LPS binding protein and endotoxin IgG antibody and most of these levels increased significantly following therapy. Thus, helminth infection is associated with attenuation of systemic inflammation and microbial translocation in T2DM and its reversal following anthelmintic therapy.